(untitled) (Journal of Biodiversity Conservation and Bioresource Management, 2018)
A study was conducted to investigate the effects of invasive weed Ageratina adenophora on the seed germination and seedling growth of Triticum aestivum, Brassica campestris and on weeds Ageratum conyzoides, Bidens pilosa, Galinsoga parviflora and Cyperus rotundus. The aqueous extracts of Ageratina plant’s part root, stem and leaf; and compost extract of Ageratina on different concentrations (control, 1, 2.5, 5 and 10%) were used to determine its effect on the seed germination, shoot and root length of Triticum aestivum, Brassica campestris and some common weed seeds under laboratory condition. The compost of A. adenophora at different doses viz. 0, 10, 20, 40 and 50g compost/kg soil was also applied to study the effect on the seed germination and seedling growth of B. campestris and T. aestivum and some weed seeds. The aqueous and compost extracts of Ageratina caused significant reduction in the seed germination and seedling length (shoot and root) which increased progressively on increasing the concentration of invasive plant’s extract. The stem and leaf extracts of A. adenophora have more inhibitory effect on the germination percentage of winter crops as compared to root extract on the test crop seeds under study. In the compost of A. adenophora, the weeds showed more reduction in comparison to the crop plants B. campestris and T. aestivum. J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 11-20